Investigation on the expression stability of common reference genes in Aurelia sp.1 under hypoxia - Gao, Xiang; Wang, Guoshan (Cellular and Molecular Biology, 2018)
RT-qPCR (Quantitative real-time polymerase chain reaction) is a reliable molecular biology technique used for gene expression detection due to its high sensibility and good reproducibility. However, suitable reference genes for RT-qPCR are often not available to investigate the expression of target genes in jellyfish under different conditions. To determine the responsible genes of jellyfish under hypoxia, primers to amplify the actin gene was designed for the amplification according to the conserved actin amino acid sequences of cnidarian. Then, we cloned and sequenced the partial cDNA sequence of Î²-actin gene containing 849 bp nucleic acids was cloned and sequenced, and the four common housekeeping genes (18S rRNA, Î²-actin, Î±-tubulin and GAPDH) were detected. To obtain suitable reference genes, we compared the four genes under normoxia and hypoxia were determined and compared using RT-qPCR. The evaluation result shows that Î±-tubulin gene can be used as single reference gene, and Î±-tubulin and Î²-actin can be served as multiple reference genes to study relative gene expression related to hypoxic tolerance of Aurelia sp.1. This research will establish foundation to reveal the molecular mechanism of jellyfish under hypoxia.